Expression of abbreviated mouse dihydrofolate reductase genes in cultured hamster cells. - Gasser, C S (1982)
We have constructed a number of abbreviated dihydrofolate reductase (DHFR) genes by using cloned mouse genomic and cDNA sequences. These genes contain 1.0 kilobase of 5' flanking genomic sequence and varying portions of the 3' non-coding region. Two of the genes contain the first two introns of the DHFR gene; the other three lack introns. Transfection of DHFR-deficient Chinese hamster ovary cells with any of these constructed genes results in cells with the DHFR+ phenotype. Treatment of the transfectants with methotrexate, a folate antagonist, leads to the emergence of methotrexate-resistant colonies which have amplified the transfected genes.